The impact of personal coaching on influenza vaccination among healthcare workers before and during COVID-19 pandemic. Issue 33 (5th August 2022) - Wong, Shuk-Ching; Chan, Veronica Wing-Man; Lam, Germaine Kit Ming; Yuen, Lithia Lai-Ha; AuYeung, Christine Ho-Yan; Li, Xin; Chen, Jonathan Hon-Kwan; Chau, Pui-Hing; Yuen, Kwok-Yung; Cheng, Vincent Chi-Chung
Abstract: Background: Without the implementation of mandatory vaccination, it was difficult to increase the influenza vaccination rate among healthcare workers. We described the strategy of personal coaching and assess its impact in increasing the influenza vaccination rate among healthcare workers in Hong Kong. Methods: Personal coaching of individual staff led by the infection control officer (ICO) and senior nursing officer (SNO) from infection control team could overcome barriers and promote on-site vaccination. The influenza vaccination rates among different categories of staff in 2016/2017 (year 1, baseline), 2017/2018 (year 2, promotion using social media), and 2018/2019 to 2020/2021 (year 3–5, promotion using personal coaching) were analysed in a healthcare region with 8490 ± 206 staff during the study period. Results: With the implementation of personal coaching, the influenza vaccination rates increased significantly among medical (65.0% vs 57.0%, p = 0.048), nursing (30.6% vs 21.1%, p < 0.001), allied health (37.0% vs 27.4%, p < 0.001), care-related supporting staff (37.7% vs 27.3%, p < 0.001), and non-professional staff (27.3% vs 22.3%, p < 0.001) in year 3 compared with year 2, and also significantly increased among all staff in year 4 (38.0% vs 34.7%, p < 0.001) and year 5 (45.2% vs 38.0%, p < 0.001) when compared with the preceding year. The increase in vaccination rate was not apparent with social media promotion alone (26.4%, year 2 vs 25.6%, year 1, p = 0.305). Conclusion: Personal coaching led by ICO and SNO significantly increased the vaccination rates among healthcare workers in 3 consecutive years. This model could be promulgated to unit heads to establish a hospital culture conducive to vaccination.